The impact of unemployment insurance and unsecured credit on business cycles - Michael Irwin (Bank of Canada, 2023)
I study how unsecured credit affects the extent to which unemployment insurance (UI) policies smooth cyclical fluctuations in aggregate consumption. To do so, I develop a real business cycle model with incomplete asset markets, frictional labor markets, and defaultable debt. Using empirically consistent unemployment dynamics over the business cycle, the model generates the cyclical properties of unsecured revolving credit balances and consumer bankruptcies in the data. The model is used to quantify the aggregate implications of a policy that extends the duration of UI during recessions. The main quantitative result of this paper is that unsecured credit amplifies the extent to which UI policies smooth aggregate consumption fluctuations over the business cycle. Extensions in the duration of UI mitigate the rise in consumer bankruptcies during recessions. They also mitigate the rise in the risk premium on unsecured borrowing, which allows households to better smooth consumption.
Keywords: E2; E21; E24; E3; E32; E44; E62; 330; Business fluctuations and cycles; Labour markets; Credit and credit aggregates; Economic models; Fiscal policy